Knowledge, Attitude and Practice of Brazilian Obstetricians Regarding Episiotomy - Cunha, Carolina Maria Pires; Katz, Leila; Lemos, Andrea; Amorim, Melania Maria (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To determine the prevalence of episiotomy and the factors associated with the knowledge, attitude and practice (KAP) of Brazilian obstetricians in relation to this procedure.Methods A KAP survey was conducted with obstetricians working in Brazil. An electronic form containing structured questions previously evaluated using the Delphi method was created in Google Docs and sent by e-mail. A multivariate logistic regression was performed to determine the principal factors associated with adequate KAP. For each dependent variable (knowledge, attitude and practice) coded as adequate (1 = yes; 0 = no), a multiple logistic regression model was developed. Binary codes (1 = yes and 0 = no) were assigned to every independent or predictor variables. Prevalence ratios (PRs) and their respective 95% confidence intervals (95%CIs) were calculated as measures of relative risk, at a significance level of 5%.Results Out of the 13 thousand physicians contacted, 1,163 replied, and 50 respondents were excluded. The mean episiotomy rate reported was of 42%. Knowledge was determined as adequate in 44.5% of the cases, attitude, in 10.9%, and practice, in 26.8% of the cases.Conclusion Most respondents had inadequate knowledge, attitudes and practices regarding episiotomy. Although some factors such as age, teaching, working in the public sector and attending congresses improved knowledge, attitude and practice, we must recognize that episiotomy rates remain well above what would be considered ideal. Adequate knowledge is more prevalent than adequate attitude or practice, indicating that improving knowledge is crucial but insufficient to change the outlook of episiotomies in Brazil.
Keywords: episiotomy; health knowledge; attitudes in health; practices in health; obstetrics; delivery; perineum